Governing of Village Fund in South Sulawesi - Samirah Dunakhir; Mukhammad Idrus (Hasanuddin Economics and Business Review, 2021)
This study aims to contribute to the development of a village fund management model in South Sulawesi. To achieve the research objectives, data collection was carried out by collecting secondary data and conducting follow-up interviews in sample villages in South Sulawesi. The analysis data that used was the descriptive qualitative analysis. The results showed that the stages in managing village funds in several villages in South Sulawesi Province had generally been carried out well. However, several obstacles are still faced by implementers in the village. Communication is one of them. Another factor that has the potential to become an obstacle in implementing the stages of village fund management is Competence. Based on the results of interviews with research informants, it was found that the backgrounds of village fund managers were mostly not in accordance with the fields that had to be handled. This in turn has an impact on the performance of the village fund managers.